COMMUNICATION FOR DEVELOPMENT AND SOCIAL CHANGE: INFLUENCING SOCIAL NORMS FOR AN INCLUSIVE SOCIETY IN MONTENEGRO - Perovic, Jelena; Obregon, Rafael (Commons. Revista de Comunicación y Ciudadanía Digital, 2017)
UNICEF and the Government of Montenegro implemented a communication strategy “It’s about ability” to challenge the existing, exclusionary practices and promote new, inclusive social norms for children with disability. Drawing on communication for development principles and social norms theory, a 2010-2013 nation-wide campaign mobilized disability rights NGOs, parents associations, media and private sector to stimulate inclusive attitudes and practices towards children with disabilities. As a result, the percentage of citizens who find it acceptable for a child with disability to attend the same class with theirs increased from 35 before the campaign to 80 percent at the end of it. Similarly, the percentage of Montenegrin citizens who find it acceptable for a child with disability to be the best friend of their child increased from 22 before the campaign to 51 percent at the end of it. The campaign was participatory, audience-centred and guided by the key communication planning principles.